2017
DOI: 10.5812/ijp.9916
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Patent Ductus Arteriosus Closure Using the Video-Assisted Thoracoscopic Surgery

Abstract: Background: Video-assisted thoracoscopic surgery (VATS) has been shown to be a safe and effective method for the patent ductus arteriosus (PDA) closure. This study aimed at evaluating the patients with PDA who underwent the VATS closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Kang et al (2012) reported that PDA ligation in preterm babies showed a higher rate in neonatal morbidity but lower rate in complication and neonatal mortality. Furthermore, a study exhibited that the VATS technique in PDA surgery reduced the adverse effects, complications and mortality rate (Esfahanizadeh et al, 2017).…”
Section: Review Of Related Literature and Studiesmentioning
confidence: 99%
“…Kang et al (2012) reported that PDA ligation in preterm babies showed a higher rate in neonatal morbidity but lower rate in complication and neonatal mortality. Furthermore, a study exhibited that the VATS technique in PDA surgery reduced the adverse effects, complications and mortality rate (Esfahanizadeh et al, 2017).…”
Section: Review Of Related Literature and Studiesmentioning
confidence: 99%